Development of web information system that communicates via SMS in FTMSK / Amer Rosyeid Abu Hassan - Abu Hassan, Amer Rosyeid (Faculty of Computer and Mathematical Sciences, 2007)
Short Messaging Service (SMS) services from application to person have became extremely popular in recent years. In an attempt to bring together the capabilities of the Internet and Mobile Technologies, the integration of the SMS function into web system will take mobility to a new level. As information exchange happen everyday in the faculty, we need a media of communication that is easy to handle and reachable to anyone who need the information. The development of Web Information System that communicates via SMS in FTMSK is the solution to this kind of matter. Lecturers or Administration Staff who can access the online web system should easily find the FTMSK community phone number to send information regarding to the faculty. The prototype design called FTMSKtoSMS can give benefits to the people want to send important information and also to the people who always fail to notice important information in faculty. Furthermore, the system should make information exchange in faculty among administration staffs, lecturers and students more interactive and valuable.